The lantern marriage operetta in one act Vocal score for rehearsal and perfomance - OFFENBACH, Jacques (Edward B. Marks Music Corporation)
Oh, what would uncle mathew saynmy former husbandnnow peter, say, will you tell us the newsnetc..